Interior of a Church, Port of Spain, Trinidad - (:unkn) unknown (G.G. Belgrave, Trinidad, 2010)
This postcard displays a photograph of the interior of a Roman Catholic church in Port of Spain, Trinidad and Tobago.
Colour: White, Yellow, Red Grey, Black and Cream Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Catholic Church--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Church architecture--Trinidad and Tobago; Interior architecture--Trinidad and Tobago; Stained glass windows--Trinidad and Tobago; Altars--Trinidad and Tobago; Architecture--Details